The forgotten helper : a Christmas story - Moore, Lorrie (Delacorte Press, 2000)
When he is left behind at the house of a very bad little girl, Santa's grouchiest elf must find a way to improve her behavior so that Santa will return the following Christmas and take him back to the North Pole.
Publ Weekly
Keywords: Fairies -- Fiction; Human behavior -- Fiction; Santa Claus -- Fiction; Christmas -- Fiction